The European Monetary Fund: internal planning and external relations – introduction - SWOBODA, A.K. (PSL Quarterly Review, 2013)
The European Monetary Fund was the subject of the Second International Seminar on European Economic and Monetary Union, held in Geneva in December of 1979. In this introduction to the proceedings, the author reviews the points of discussion and offers some introductory remarks. JEL: F33, F36